The Impact of Gadget Use on the Social Development of Elementary School Students - Yanti, Rasmi; Ismiyanti, Yulina (BASICA, 2025)
This study aims to determine the positive and negative impacts of using handphone both at school and at home, on the social development of fifth grade students of Al Fattah Islamic Elementary School. The method used in this study is a qualitative descriptive research type that focuses on case studies. The subjects studied were fifth grade students of Al Fattah Islamic Elementary School. Data collection was conducted through observation, questionnaires, and interviews condensation with 10 fifth grade students selected using purposive sampling techniques. The data analysis technique used was the Miles, Huberman, & Saldana, namely data, data presentation, and drawing conclusions. The results of the study show that the impact of mobile phone use on students includes positive and negative impacts, where the negative impacts are greater than the positive impacts. The negative impacts of handphone use are that it makes students dependent, reduces students' social interaction with peers and the surrounding environment, students are less active in discussions or group work, students often say and behave impolitely, and students become indifferent to the surrounding environment and tend to be more interested in virtual interactions than direct interactions so that they become passive individuals and develop towards anti-social individuals. While the positive impacts of handphone use are that students find it easier to communicate with friends and find information or learning materials that are not yet known.